Reflective photomask blanks and reflective photomasks

The reflective photomask blank and photomask with an indium oxide absorbing layer and a tantalum oxide outermost layer address the challenges of projection effect and hydrogen radical resistance, resulting in improved transfer performance and stability for EUV lithography.

JP7662307B2Active Publication Date: 2025-04-15TEKSCEND PHOTOMASK CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020113230
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-06-30
Publication Date
2025-04-15
Estimated Expiration
2040-06-30

AI Technical Summary

Technical Problem

Current reflective photomasks for EUV lithography face challenges such as increased line edge roughness and reduced contrast at the edge portions due to the projection effect, and they lack resistance to hydrogen radicals, leading to instability in transfer patterns.

Method used

A reflective photomask blank and photomask with a laminated structure comprising an absorbing layer made of indium oxide and an outermost layer with materials like tantalum oxide, which reduces the projection effect and enhances hydrogen radical resistance.

Benefits of technology

The solution improves transfer performance on semiconductor substrates by reducing the projection effect and maintaining stable transfer patterns even in hydrogen radical environments, thereby enhancing the overall performance and longevity of the reflective photomask.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662307000004
    Figure 0007662307000004
  • Figure 0007662307000005
    Figure 0007662307000005
  • Figure 0007662307000006
    Figure 0007662307000006
Patent Text Reader

Abstract

To provide a reflective photomask blank and a reflective photomask which suppress or lighten a shadowing effect of a reflective photomask for patterning transfer which uses light having a wavelength in an extreme-ultraviolet region as a light source, and have high resistance against hydrogen radical.SOLUTION: A reflective photomask blank 10 comprising: a substrate 1; a reflection part 6 which is formed on the substrate 1 and reflects incident light; and a low reflection part 7 which absorbs incident light formed on the reflection part 6. The low reflection part 7 consists of an absorption layer 4 and an outermost layer 5, and at least one layer of the absorption layer 4 contains indium oxide, and the outermost layer 5 contains any one or more of tantalum, aluminum, silicon, palladium, zirconium, hafnium, niobium, chromium, platinum, yttrium, nickel, lead, titanium, gallium and bismuth, and oxide, nitride, fluoride, boride, oxynitride, oxyboride and boride oxynitride thereof.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a reflective photomask for use in lithography using light in the ultraviolet region as a light source, and a reflective photomask blank for producing the same. [Background technology]

[0002] In the manufacturing process of semiconductor devices, the demand for miniaturization of photolithography technology is increasing along with the miniaturization of semiconductor devices. The minimum resolution dimension of the transfer pattern in photolithography depends heavily on the wavelength of the exposure light source, and the shorter the wavelength, the smaller the minimum resolution dimension can be. For this reason, the exposure light source is being replaced from the conventional ArF excimer laser light with a wavelength of 193 nm to light in the EUV (Extreme Ultra Violet) region with a wavelength of 13.5 nm.

[0003] Light in the EUV region is absorbed at a high rate by most substances, so a reflective photomask is used as a photomask for EUV exposure (EUV mask) (see, for example, Patent Document 1). Patent Document 1 discloses an EUV photomask obtained by forming a reflective layer made of a multilayer film in which molybdenum (Mo) layers and silicon (Si) layers are alternately laminated on a glass substrate, forming a light absorbing layer mainly composed of tantalum (Ta) thereon, and forming a pattern on this light absorbing layer.

[0004] Furthermore, as mentioned above, EUV lithography cannot use refractive optics that utilize the transmission of light, so the optical components of the exposure machine are reflective (mirrors) rather than lenses. This creates a problem in that the incident light and reflected light on the reflective photomask (EUV mask) cannot be designed to be coaxial, so EUV lithography normally employs a method in which the optical axis is tilted 6 degrees from the vertical direction of the EUV mask, and the reflected light reflected at an angle of minus 6 degrees is guided to the semiconductor substrate.

[0005] As such, in EUV lithography, the optical axis is tilted via a mirror, which is known to cause a problem known as the "projection effect," in which the EUV light incident on the EUV mask casts a shadow on the mask pattern (patterned light-absorbing layer) of the EUV mask.

[0006] Current EUV mask blanks use a tantalum (Ta)-based film with a thickness of 60 nm to 90 nm as the light absorption layer. When performing pattern transfer exposure with an EUV mask fabricated using this mask blank, there is a risk of a decrease in contrast at the shadow edge of the mask pattern depending on the relationship between the incident direction of the EUV light and the orientation of the mask pattern. This can lead to problems such as increased line edge roughness of the transferred pattern on the semiconductor substrate and inability to form the line width to the targeted dimension, resulting in a deterioration of transfer performance.

[0007] Therefore, reflective photomask blanks are being considered in which the light absorption layer is changed from tantalum (Ta) to a material with high absorptivity (extinction coefficient) for EUV light, or a material with high absorptivity is added to tantalum (Ta). For example, Patent Document 2 describes a reflective photomask blank in which the light absorption layer is made of a material containing 50 atomic % (at %) or more of Ta as the main component and further containing at least one element selected from Te, Sb, Pt, I, Bi, Ir, Os, W, Re, Sn, In, Po, Fe, Au, Hg, Ga, and Al.

[0008] Furthermore, it is known that mirrors are contaminated by by-products of EUV generation (e.g., Sn) and carbon. Accumulation of contaminants on the mirror can reduce the reflectivity of the mirror surface, lowering the throughput of the lithography apparatus. To address this problem, Patent Document 3 discloses a method of generating hydrogen radicals within the apparatus, reacting the hydrogen radicals with the contaminants, and removing the contaminants from the mirror.

[0009] However, in the reflective photomask blank described in Patent Document 2, there is no consideration as to whether the light absorbing layer has resistance to hydrogen radicals (hydrogen radical resistance). Therefore, the transfer pattern (mask pattern) formed on the light absorbing layer by introduction into an EUV exposure tool cannot be stably maintained, and as a result, there is a possibility that the transferability may deteriorate. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2011-176162 A [Patent Document 2] JP 2007-273678 A [Patent Document 3] JP 2011-530823 A Summary of the Invention [Problem to be solved by the invention]

[0011] Therefore, an object of the present invention is to provide a reflective photomask blank and a reflective photomask that suppress or reduce the projection effect of a reflective photomask for patterning transfer using light with a wavelength in the extreme ultraviolet region as a light source, and that are highly resistant to hydrogen radicals. [Means for solving the problem]

[0012] In order to solve the above problems, a reflective photomask blank according to one embodiment of the present invention is a reflective photomask blank for producing a reflective photomask for pattern transfer using extreme ultraviolet light as a light source, comprising: a substrate; a reflective portion formed on the substrate for reflecting incident light; and a low-reflection portion formed on the reflective portion for absorbing incident light, wherein the low-reflection portion is a laminated structure of at least two layers composed of an absorption layer and an outermost layer, and at least one layer of the absorption layer in the low-reflection portion is an oxidized layer. The low-reflection portion contains indium, and the outermost layer of the low-reflection portion contains one or more of tantalum (Ta), aluminum (Al), silicon (Si), palladium (Pd), zirconium (Zr), hafnium (Hf), niobium (Nb), chromium (Cr), platinum (Pt), yttrium (Y), nickel (Ni), lead (Pb), titanium (Ti), gallium (Ga), and bismuth (Bi), as well as oxides, nitrides, fluorides, borides, oxynitrides, oxyborides, and boron oxynitrides thereof.

[0013] A reflective photomask according to one aspect of the present invention is a reflective photomask for pattern transfer using extreme ultraviolet light as a light source, comprising: a substrate; a reflective portion formed on the substrate for reflecting incident light; and a low-reflection portion formed on the reflective portion for absorbing the incident light, the low-reflection portion being a laminated structure of at least two layers composed of an absorption layer and an outermost layer, at least one layer of the absorption layer of the low-reflection portion contains indium oxide, and the outermost layer of the low-reflection portion is a laminated structure of at least two layers composed of an absorption layer and an outermost layer, at least one layer of the absorption layer of the low-reflection portion contains indium oxide, The surface layer is characterized by containing one or more of tantalum (Ta), aluminum (Al), silicon (Si), palladium (Pd), zirconium (Zr), hafnium (Hf), niobium (Nb), chromium (Cr), platinum (Pt), yttrium (Y), nickel (Ni), lead (Pb), titanium (Ti), gallium (Ga), and bismuth (Bi), as well as oxides, nitrides, fluorides, borides, oxynitrides, oxyborides, and oxynitride boride thereof. Effect of the Invention

[0014] According to one aspect of the present invention, a reflective photomask that has improved transfer performance to a semiconductor substrate in patterning using light with a wavelength in the extreme ultraviolet region as a light source and that can be used even in a hydrogen radical environment can be expected. In other words, the reflective photomask blank and reflective photomask according to one aspect of the present invention suppress or reduce the projection effect of a reflective photomask for patterning transfer using light with a wavelength in the extreme ultraviolet region as a light source, and have resistance to hydrogen radicals. [Brief description of the drawings]

[0015] [Figure 1] 1 is a schematic cross-sectional view showing a structure of a reflective photomask blank according to an embodiment of the present invention. [Diagram 2] 1 is a schematic cross-sectional view showing a structure of a reflective photomask according to an embodiment of the present invention. [Diagram 3] 1 is a map showing the refractive index n and the extinction coefficient k at the wavelength of EUV light. [Figure 4] FIG. 1 is a schematic cross-sectional view showing a structure of a reflective photomask blank according to an embodiment of the present invention. [Diagram 5] 1A to 1C are schematic cross-sectional views showing a manufacturing process of a reflective photomask according to an embodiment of the present invention. [Figure 6] 1A to 1C are schematic cross-sectional views showing a manufacturing process of a reflective photomask according to an embodiment of the present invention. [Figure 7] 1A to 1C are schematic cross-sectional views showing a manufacturing process of a reflective photomask according to an embodiment of the present invention. [Figure 8] 1A to 1C are schematic cross-sectional views showing a manufacturing process of a reflective photomask according to an embodiment of the present invention. [Figure 9] 1 is a schematic cross-sectional view showing a structure of a reflective photomask according to an embodiment of the present invention. [Figure 10] FIG. 2 is a schematic plan view showing a 64 nm line width LS pattern for transfer evaluation according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, embodiments of the present invention will be described with reference to the drawings, but the present invention is not limited to the embodiments shown below. In the embodiments shown below, technically preferable limitations are imposed for carrying out the present invention, but these limitations are not essential requirements for the present invention.

[0017] Fig. 1 is a schematic cross-sectional view showing the structure of a reflective photomask blank 10 according to an embodiment of the present invention. Fig. 2 is a schematic cross-sectional view showing the structure of a reflective photomask 20 according to an embodiment of the present invention. Here, the reflective photomask 20 according to the embodiment of the present invention shown in Fig. 2 is formed by patterning the low-reflection portion 7 of the reflective photomask blank 10 according to the embodiment of the present invention shown in Fig. 1.

[0018] (Overall structure) 1, a reflective photomask blank 10 according to an embodiment of the present invention includes a substrate 1, a reflective layer 2 formed on the substrate 1, and a capping layer 3 formed on the reflective layer 2. As a result, a reflective portion 6 having the reflective layer 2 and the capping layer 3 is formed on the substrate 1. A low-reflection portion 7 is provided on the reflective portion 6, and the low-reflection portion 7 is composed of at least two layers, one of which is an absorbing layer 4, and an outermost layer 5 is provided on the absorbing layer 4.

[0019] (substrate) For example, a flat Si substrate, a synthetic quartz substrate, etc. can be used for the substrate 1 according to the embodiment of the present invention. In addition, low thermal expansion glass containing titanium can be used for the substrate 1, but the present invention is not limited to these as long as the material has a small thermal expansion coefficient.

[0020] (reflective layer) The reflective layer 2 according to the embodiment of the present invention may be a multilayer reflective film made of a combination of materials having significantly different refractive indices for EUV light, as long as it reflects the EUV light (extreme ultraviolet light) that is the exposure light. The multilayer reflective film may be formed by repeatedly stacking layers of a combination of Mo (molybdenum) and Si (silicon), or Mo (molybdenum) and Be (beryllium), for example, for about 40 periods.

[0021] (capping layer) The capping layer 3 according to the embodiment of the present invention is made of a material that is resistant to dry etching performed when forming a transfer pattern (mask pattern) on the absorption layer 4, and functions as an etching stopper that prevents damage to the reflective layer 2 when etching the absorption layer 4. The capping layer 3 is made of, for example, Ru (ruthenium). Here, depending on the material of the reflective layer 2 and the etching conditions, the capping layer 3 may not be formed. Although not shown, a back conductive film can be formed on the surface of the substrate 1 on which the reflective layer 2 is not formed. The back conductive film is a film for fixing the reflective photomask 20 by utilizing the principle of an electrostatic chuck when the reflective photomask 20 is placed in an exposure machine.

[0022] (Absorption layer) As shown in FIG. 2, by removing a part of the absorbing layer 4 of the reflective photomask blank 10, that is, by patterning the absorbing layer 4, an absorbing pattern (low absorbing portion pattern) 7a of the reflective photomask 20 is formed. In EUV lithography, EUV light is incident at an angle and reflected by the reflecting portion 6, but due to a projection effect in which the absorbing pattern 7a obstructs the light path, the transfer performance onto the wafer (semiconductor substrate) may deteriorate. This deterioration in transfer performance can be reduced by reducing the thickness of the absorbing layer 4 that absorbs EUV light. In order to reduce the thickness of the absorbing layer 4, it is preferable to use a material that is more absorbent for EUV light than conventional materials, that is, a material with a high extinction coefficient k at a wavelength of 13.5 nm.

[0023] Figure 3 is a graph showing the optical constants of some metal materials for EUV light with a wavelength of 13.5 nm. The horizontal axis of Figure 3 represents the refractive index n, and the vertical axis represents the extinction coefficient k. The extinction coefficient k of tantalum (Ta), which is the main material of the conventional absorption layer 4, is 0.041. If a material has a larger extinction coefficient k, it is possible to make the thickness of the absorption layer 4 thinner than before. Materials that satisfy the above-mentioned extinction coefficient k include, for example, silver (Ag), platinum (Pt), indium (In), cobalt (Co), tin (Sn), nickel (Ni), and tellurium (Te), as shown in FIG.

[0024] The intensity of reflected light from the reflective portion 6 is Rm, and the intensity of reflected light from the low-reflective portion 7 is Ra. The optical density (OD) value, which is an index representing the contrast in light intensity between the reflective portion 6 and the low-reflective portion 7, is defined by the following formula (1). OD = -log(Ra / Rm) Equation (1) The larger the OD value, the better the contrast and the higher the transferability. For pattern transfer, OD>1 is necessary, but based on the above comparison with the conventional method, an OD value of 1.5 or more is more preferable.

[0025] As described above, a compound material mainly composed of Ta has been applied to the absorption layer 4 of the conventional EUV reflective photomask. In this case, to obtain an OD value of 1 or more, the thickness of the absorption layer 4 needs to be 40 nm or more, and to obtain an OD value of 2 or more, the thickness of the absorption layer 4 needs to be 70 nm or more. The extinction coefficient k of Ta is 0.041, but by applying a material containing indium (In) and oxygen (O) with an extinction coefficient k of 0.06 or more to the absorption layer 4, it is possible to thin the thickness of the absorption layer 4 to 17 nm if the OD value is at least 1 or more, and to reduce the thickness of the absorption layer 4 to 45 nm or less if the OD value is 2 or more. However, if the thickness of the absorption layer 4 exceeds 45 nm, the projection effect will be about the same as that of a conventional absorption layer 4 with a thickness of 60 nm formed from a compound material mainly composed of Ta.

[0026] Therefore, it is preferable that the absorption layer 4 according to the embodiment of the present invention is mainly composed of a material containing indium (In) and oxygen (O) and has a film thickness of 17 nm to 45 nm. In other words, when the film thickness of the absorption layer 4 is within the range of 17 nm to 45 nm, the projection effect can be sufficiently reduced and the transfer performance is improved compared to the conventional absorption layer 4 formed of a compound material mainly composed of Ta. The above-mentioned "main component" refers to a component that is contained in an amount of 50 atomic % or more relative to the number of atoms in the entire absorbing layer.

[0027] Furthermore, in order to transfer a fine pattern, it is desirable to have a high contrast between the intensity of the light reflected from the reflective portion 6 and the low-reflective portion 7. Therefore, it is more preferable that the OD value of the absorbing layer 4 is 1.5 or more. The material containing indium (In) and oxygen (O) for forming the absorption layer 4 is preferably between 1:1 and 1:1.5. In other words, the atomic ratio (O / In) of oxygen (O) to indium (In) in the absorption layer 4 is preferably 1 or more and 1.5 or less. This range is based on the fact that an atomic ratio of less than 1 leads to a decrease in heat resistance, and an atomic ratio of 1.5 is the maximum stoichiometric ratio.

[0028] 1 and 2 show a single-layered absorption layer 4, but the absorption layer 4 according to the present embodiment is not limited thereto. The absorption layer 4 according to the present embodiment may be, for example, one or more absorption layers, i.e., a multi-layered absorption layer. That is, the absorption layer 4 according to the present embodiment may be divided into a plurality of layers, and even in this case, the total thickness of the absorption layers 4 is preferably 17 nm or more and 45 nm or less.

[0029] Furthermore, the material constituting the absorbing layer 4 preferably contains 50 atomic % or more of indium (In) and oxygen (O) in total. This is because, although there is a possibility that the EUV light absorbency may decrease if the absorbing layer 4 contains components other than indium (In) and oxygen (O), if the components other than indium (In) and oxygen (O) are less than 50 atomic %, the decrease in EUV light absorbency is very slight, and there is almost no decrease in performance as the absorbing layer 4 of the EUV mask.

[0030] The absorption layer 4 is formed on the capping layer 3. Examples of the material other than indium (In) and oxygen (O) include beryllium (Be), calcium (Ca), scandium (Sc), vanadium (V), manganese (Mn), iron (Fe), cobalt (Co), copper (Cu), ruthenium (Ru), silver (Ag), barium (Ba), iridium (Ir), gold (Au), silicon (Si), germanium (Ge), hafnium (Hf), tantalum (Ta), aluminum (Al), palladium (Pd), zirconium (Zr), niobium (Nb), and chromium (Cu). It may be composed of a material containing less than 50 atomic % of at least one selected from chromium (Cr), platinum (Pt), yttrium (Y), nickel (Ni), lead (Pb), titanium (Ti), gallium (Ga), tellurium (Te), tungsten (W), molybdenum (Mo), tin (Sn), arsenic (As), strontium (Sr), technetium (Tc), rhodium (Rh), rhenium (Re), osmium (Os), and radium (Ra), as well as their oxides, nitrides, fluorides, borides, oxynitrides, oxyborides, and boron oxynitride compounds.

[0031] The material constituting the absorption layer 4 may contain, for example, beryllium (Be), calcium (Ca), scandium (Sc), vanadium (V), manganese (Mn), iron (Fe), copper (Cu), germanium (Ge), arsenic (As), strontium (Sr), technetium (Tc), rhodium (Rh), barium (Ba), tungsten (W), rhenium (Re), osmium (Os), gold (Au), or the like, which can improve the roughness, in-plane dimensional uniformity, and in-plane uniformity of the transferred image, and can be a sufficiently amorphous material.

[0032] In addition, the material constituting the absorption layer 4 can contain, for example, silver (Ag), nickel (Ni), tellurium (Te), tin (Sn), etc., so that the material has an extinction coefficient k greater than that of tantalum (Ta), which is the conventional main material. In addition, the material constituting the absorption layer 4 can contain, for example, tantalum (Ta), silicon (Si), zirconium (Zr), hafnium (Hf), niobium (Nb), yttrium (Y), lead (Pb), gallium (Ga), etc., making it less likely to react with hydrogen radicals and more resistant to hydrogen radicals.

[0033] In addition, the material constituting the absorption layer 4 can contain, for example, aluminum (Al), chromium (Cr), zirconium (Zr), etc., so that the material has low reactivity with chemicals such as SPM and APM that are generally used for mask cleaning, and can be made more resistant to cleaning. Furthermore, the material constituting the absorption layer 4 contains, for example, silicon nitride (SiN), tantalum oxide (TaO), or the like, and can be a material that has high light absorption at wavelengths of 190 nm to 260 nm and improves the contrast of the inspection light.

[0034] In addition, the material constituting the absorption layer 4 can contain, for example, cobalt (Co), ruthenium (Ru), iridium (Ir), gold (Au), palladium (Pd), platinum (Pt), molybdenum (Mo), etc., and can be a material that has a refractive index n of less than 0.95 for a wavelength of 13.5 nm and improves the phase shifting properties. Although examples of the effects of the materials that can be contained in the absorbent layer 4 have been described above, the effects of each material are not limited to the above examples, and each material may have a plurality of effects.

[0035] Furthermore, since the reflective photomask 20 is exposed to a hydrogen radical environment, it cannot withstand long-term use unless it is made of a light absorbing material with high hydrogen radical resistance. In this embodiment, a material with high hydrogen radical resistance is defined as a material with a film reduction rate of 0.1 nm / s or less in a hydrogen radical-rich environment generated by generating hydrogen plasma using microwave plasma with a power of 1 kW in a vacuum of 0.36 millibar (mbar) or less. Among materials that satisfy the combination of nk values, indium (In) alone is known to have low resistance to hydrogen radicals.

[0036] In the evaluation test of the film reduction rate shown in Table 1, the film reduction rate was measured multiple times, and a case in which the film reduction rate was 0.1 nm / s or less in all the measurements was evaluated as "○". A case in which there was a film reduction of several nm immediately after the start of the hydrogen radical treatment but the film reduction rate was 0.1 nm / s or less thereafter was evaluated as "△". A case in which the film reduction rate exceeded 0.1 nm / s in all the measurements was evaluated as "×". The atomic ratio (O / In ratio) was measured by EDX (energy dispersive X-ray analysis) on a material formed into a film having a thickness of 1 μm.

[0037] The evaluation results are shown in Table 1.

[0038] [Table 1]

[0039] When the O / In ratio was 1.0, the rate of film loss was large, and when the O / In ratio was 1.5, film loss occurred, although only slightly.

[0040] (top layer) In order to improve hydrogen radical resistance, it is effective to provide a highly resistant material in the outermost layer. In order not to decrease hydrogen radical resistance, it is desirable that the outermost layer 5 is formed of a material containing at least 80 atomic % or more of a material having hydrogen radical resistance. Therefore, it is desirable that the outermost layer 5 is composed of a material containing at least 80 atomic % or more of a material containing at least one of tantalum (Ta), aluminum (Al), silicon (Si), palladium (Pd), zirconium (Zr), hafnium (Hf), niobium (Nb), chromium (Cr), platinum (Pt), yttrium (Y), nickel (Ni), lead (Pb), titanium (Ti), gallium (Ga), and bismuth (Bi), as well as oxides, nitrides, fluorides, borides, oxynitrides, oxyborides, and oxynitride boride thereof. The material constituting the outermost layer 5 may contain materials other than the above-mentioned materials.

[0041] Since the film thickness of the low reflection portion 7 is the combined film thickness of the absorbing layer 4 and the outermost layer 5, there is a concern that the projection effect may increase. Therefore, it is desirable that the total layer thickness of the absorbing layer 4 and the outermost layer 5 is 60 nm or less. Furthermore, when the outermost layer 5 is formed of a material having sufficient hydrogen radical resistance, the film thickness of the outermost layer 5 is preferably 1 nm or more in order to obtain a stable film thickness distribution. The absorbing layer 4 was made of indium oxide (O / In=1.5) and the outermost layer 5 was made of tantalum oxide (TaO), and an evaluation test was carried out on the film reduction rate at each layer thickness of the outermost layer 5. The evaluation criteria for this evaluation were the same as those in the evaluation test on the film reduction rate shown in Table 1.

[0042] The results are shown in Table 2.

[0043] [Table 2]

[0044] As shown in Table 2, when the tantalum oxide (TaO) film thickness was 1 nm, 5 nm, or 10 nm, no film loss occurred.

[0045] The outermost layer 5 is formed on the absorbing layer 4, and it is preferable that the film quality is sufficiently amorphous in order to ensure the roughness and in-plane dimensional uniformity of the absorbing pattern 7a after etching, and the in-plane uniformity of the transferred image. Therefore, the material constituting the outermost layer 5 may be, for example, a material containing at least one element selected from beryllium (Be), calcium (Ca), scandium (Sc), vanadium (V), manganese (Mn), iron (Fe), cobalt (Co), copper (Cu), germanium (Ge), arsenic (As), strontium (Sr), molybdenum (Mo), technetium (Tc), ruthenium (Ru), rhodium (Rh), silver (Ag), barium (Ba), tungsten (W), rhenium (Re), osmium (Os), iridium (Ir), gold (Au), and radium (Ra), as well as their oxides, nitrides, fluorides, borides, oxynitrides, oxyborides, and oxynitride boride, in a composition ratio of less than 20%.

[0046] Examples of the reflective photomask blank and the reflective photomask according to the present invention will be described below.

[0047] [Example 1] As shown in Fig. 4, a multilayer reflective film 12 was formed by stacking 40 layers of a laminate film made of a pair of silicon (Si) and molybdenum (Mo) on a synthetic quartz substrate 11 having low thermal expansion characteristics. The thickness of the multilayer reflective film 12 was 280 nm. Next, a capping layer 13 made of ruthenium (Ru) was formed as an intermediate film to a thickness of 2.5 nm on the multilayer reflective film 12. As a result, a reflective portion 17 having the multilayer reflective film 12 and the capping layer 13 was formed on the substrate 11. Next, the absorbing layer 14 was formed on the capping layer 13 with a homogeneous material of indium oxide and germanium in a ratio of 30:70 to a thickness of 47 nm. The atomic ratio of indium to oxygen was measured by XPS (X-ray photoelectron spectroscopy) to be 1:1.5. The crystallinity of the absorbing layer 14 was measured by XRD (X-ray diffraction) and found to be amorphous.

[0048] Next, the outermost layer 15 made of tantalum oxide was formed to a thickness of 2 nm on the absorbing layer 14. As a result, a low-reflecting portion 18 having the absorbing layer 14 and the outermost layer 15 was formed on the reflective portion 17. Next, a back conductive film 16 made of chromium nitride was formed to a thickness of 100 nm on the side of the substrate 11 on which the multilayer reflective film 12 was not formed, thereby producing the reflective photomask blank 100 of Example 1. A multi-target sputtering device was used to deposit each film on the substrate 11. The thickness of each film was controlled by the sputtering time.

[0049] Next, a method for producing the reflective photomask 200 will be described with reference to FIGS. As shown in FIG. 5, a positive chemically amplified resist (SEBP9012: manufactured by Shin-Etsu Chemical Co., Ltd.) was spin-coated to a thickness of 120 nm on the low-reflection portion 18 of the reflective photomask blank 100, and baked at 110° C. for 10 minutes to form a resist film 19. Next, a predetermined pattern was drawn on the resist film 19 formed of a positive chemically amplified resist using an electron beam lithography machine (JBX3030: manufactured by JEOL Ltd.). After that, a baking process was performed at 110° C. for 10 minutes, and then spray development (SFG3000: manufactured by Sigma Meltec Co., Ltd.) was performed. As a result, a resist pattern 19a was formed as shown in FIG. 6.

[0050] Next, using the resist pattern 19a as an etching mask, the outermost layer 15 was patterned by dry etching mainly using a fluorine-based gas, to form an outermost layer pattern on the outermost layer 15 as shown in FIG. Next, the absorbing layer 14 was patterned by dry etching mainly using a chlorine-based gas to form an absorbing pattern, thereby forming a low-reflection portion pattern 18a as shown in FIG. Next, the remaining resist pattern 19a was peeled off to produce a reflective photomask 200 according to this embodiment as shown in FIG.

[0051] Next, the reflective photomask 200 according to this embodiment was immersed in sulfuric acid at 80° C. for 10 minutes, and then immersed in a cleaning tank filled with a cleaning solution of ammonia, hydrogen peroxide, and water in a ratio of 1:1:20 for 10 minutes using 500 W megasonics, and washed with running water for 10 minutes. After that, the film thickness was measured with an atomic force microscope (AFM) and compared with the film thickness at the time of film formation, but no change was observed in the film thickness. In this embodiment, the low reflection portion pattern 18a formed in the low reflection portion 18 includes a 64 nm line-and-space (LS) pattern, a 200 nm line-width LS pattern for measuring the thickness of the absorber layer 14 using an AFM, and a 4 mm square low reflection portion removed portion for measuring the EUV reflectance on a reflective photomask 200 for transfer evaluation. The 64 nm line-width LS pattern was designed in each of the x and y directions as shown in FIG. 10 so that the influence of the projection effect caused by oblique irradiation of EUV can be easily seen.

[0052] [Example 2] The absorption layer 14 was made of a homogeneous material with a 50:50 ratio of indium oxide and germanium, and was deposited to a thickness of 47 nm. The atomic ratio of indium to oxygen was measured by XPS (X-ray photoelectron spectroscopy) to be 1:1.5. Next, the outermost layer 15 made of tantalum oxide was formed on the absorbing layer 14 to a thickness of 2 nm. As a result, the total thickness of the low-reflection portion 18 was 49 nm. The reflective photomask blank 100 and the reflective photomask 200 of Example 2 were produced in the same manner as in Example 1, except for the formation of the absorbing layer 14 and the outermost layer 15.

[0053] [Example 3] The absorption layer 14 was made of a homogeneous material with a 50:50 ratio of indium oxide and germanium, and was deposited to a thickness of 33 nm. The atomic ratio of indium to oxygen was measured by XPS (X-ray photoelectron spectroscopy) to be 1:1.5. Next, the outermost layer 15 made of tantalum oxide was formed on the absorbing layer 14 to a thickness of 2 nm. As a result, the total thickness of the low-reflection portion 18 was 35 nm. The reflective photomask blank 100 and the reflective photomask 200 of Example 3 were produced in the same manner as in Example 1, except for the formation of the absorbing layer 14 and the outermost layer 15.

[0054] [Example 4] The absorption layer 14 was made of indium oxide and was deposited to a thickness of 26 nm. The atomic ratio of indium to oxygen was 1:1.5 as measured by XPS (X-ray photoelectron spectroscopy). Next, the outermost layer 15 made of tantalum oxide was formed on the absorbing layer 14 to a thickness of 2 nm. As a result, the total thickness of the low-reflection portion 18 was 28 nm. The reflective photomask blank 100 and the reflective photomask 200 of Example 4 were produced in the same manner as in Example 1, except for the formation of the absorbing layer 14 and the outermost layer 15.

[0055] [Example 5] The absorption layer 14 was made of indium oxide and was deposited to a thickness of 26 nm. The atomic ratio of indium to oxygen was 1:1.5 as measured by XPS (X-ray photoelectron spectroscopy). Next, the outermost layer 15 made of bismuth (Bi) was formed on the absorbing layer 14 to a thickness of 2 nm. As a result, the total thickness of the low-reflection portion 18 was 28 nm. The reflective photomask blank 100 and the reflective photomask 200 of Example 5 were produced in the same manner as in Example 1, except for the formation of the absorbing layer 14 and the outermost layer 15.

[0056] [Comparative Example 1] The absorption layer 14 was made of indium oxide and was deposited to a thickness of 26 nm. The atomic ratio of indium to oxygen was 1:1.5 as measured by XPS (X-ray photoelectron spectroscopy). The outermost layer 15 was not formed. The reflective photomask blank 100 and the reflective photomask 200 of Comparative Example 1 were produced in the same manner as in Example 1 except for the above.

[0057] [Comparative Example 2] The absorbing layer 14 was formed of tantalum nitride and was deposited to a thickness of 58 nm. The outermost layer 15 was formed of tantalum oxide and was deposited to a thickness of 2 nm. This comparative example is based on the assumption of a conventional reflective photomask having an existing film mainly composed of tantalum. The reflective photomask blank 100 and the reflective photomask 200 of Comparative Example 2 were produced in the same manner as in Example 1, except for the deposition of the absorbing layer 14 and the outermost layer 15. The reflectance Rm of the reflective layer region and the reflectance Ra of the low reflection region of the reflective photomask 200 produced in the above-mentioned Examples and Comparative Examples were measured using a reflectance measuring device using EUV light. The reflectance Rm was measured at a 4 mm square absorber layer removal portion. From the measurement results, the OD value was calculated using the above-mentioned formula (1).

[0058] (Hydrogen radical resistance) The reflective photomask 200 produced in the examples and comparative examples was placed in a hydrogen radical environment with a hydrogen pressure of 0.36 mbar or less at a power of 1 kW using microwave plasma. The change in film thickness of the absorption layer 4 after hydrogen radical treatment was confirmed using an AFM. The measurement was performed on a LS pattern with a line width of 200 nm. In this case, the hydrogen radical resistance was evaluated as "○" when the film loss rate was 0.1 nm / s or less, and was evaluated as "◎" when it was particularly excellent. In addition, the film loss rate was 0.1 nm / s or less after the start of the hydrogen radical treatment, but was evaluated as "△", and the film loss rate was over 0.1 nm / s in all cases. In this example, if the evaluation was "○" or higher, there was no problem in use, so it was evaluated as passing.

[0059] (Wafer exposure evaluation) Using an EUV exposure tool (NXE3300B, manufactured by ASML), the low reflection portion pattern 18a of the reflective photomask 200 produced in the examples and comparative examples was transferred and exposed onto a semiconductor wafer coated with an EUV positive chemically amplified resist. At this time, the exposure dose was adjusted so that the LS pattern in the x direction in FIG. 10 was transferred as designed. After that, the transferred resist pattern was observed and line width was measured using an electron beam dimension measuring device to confirm the resolution. In this case, the HV-bias was rated as "△" for the existing film with a thickness of 7.3 nm, "○" for less than 7.3 nm, and "◎" for 4.5 nm or less, while the OD value was rated as "○" for 1.5 or more, and "◎" for 2 or more. For HV-bias, if the evaluation was "△" or higher, there were no problems with use, so it was considered to have passed. For OD value, if the evaluation was "○" or higher, there were no problems with use, so it was considered to have passed.

[0060] The evaluation results are shown in Table 3.

[0061] [Table 3]

[0062] Table 3 shows the mask characteristics and resist pattern dimensions on the wafer for the existing Ta-based film in Comparative Example 2, in which the absorption layer 14 is tantalum nitride with a thickness of 58 nm and the outermost layer 15 is tantalum oxide with a thickness of 2 nm. With the reflective photomask 200 of Comparative Example 2, an OD value of 1.54 was obtained, which was a contrast that allowed pattern transfer. As a result of patterning using EUV light, the HV bias (horizontal-vertical dimension difference) was 7.3 nm, and although the image was resolved, the shadowing effect was large, resulting in low transferability.

[0063] Table 3 shows the mask characteristics and resist pattern dimensions on the wafer for a photomask in Example 1, in which the absorption layer 14 is made of a material consisting of indium oxide and germanium (mixture ratio 30:70) and has a thickness of 47 nm, and the outermost layer 15 is made of tantalum oxide and has a thickness of 2 nm. With the reflective photomask 200 of Example 1, no change in film thickness was observed in response to hydrogen radicals, and good results were obtained. The OD value was 1.73, and a contrast capable of pattern transfer was obtained. As a result of patterning using EUV light, the HV bias was 5.3 nm, and superior pattern transferability was obtained compared to Comparative Example 2.

[0064] Table 3 shows the mask characteristics and resist pattern dimensions on the wafer for a photomask in Example 2, in which the absorbing layer 14 is made of a material consisting of indium oxide and germanium (mixture ratio 50:50) and has a thickness of 47 nm, and the outermost layer 15 is made of tantalum oxide and has a thickness of 2 nm. In the case of the reflective photomask 200 of Example 2, no change in film thickness was observed with respect to hydrogen radicals, and good results were obtained. The OD value was 2.33, and a higher contrast was obtained than in Example 1. As a result of patterning using EUV light, the HV bias was 7.0 nm, which is a result that the shadowing effect can be reduced and pattern transferability can be improved compared to Comparative Example 2, but the performance is somewhat inferior to that of Example 1.

[0065] Table 3 shows the mask characteristics and resist pattern dimensions on the wafer for a photomask in Example 3, in which the absorbing layer 14 is made of a material consisting of indium oxide and germanium (mixture ratio 50:50) and has a thickness of 33 nm, and the outermost layer 15 is made of tantalum oxide and has a thickness of 2 nm. In the case of the reflective photomask 200 of Example 3, no change in film thickness was observed with respect to hydrogen radicals, and good results were obtained. The OD value was 1.55, and a contrast capable of pattern transfer was obtained. As a result of patterning using EUV light, the HV bias was 4.1 nm, which was a result that the shadowing effect could be reduced and the pattern transferability could be greatly improved compared to Comparative Example 2, and it was found that both the OD value and the HV bias were improved by making the film thinner compared to Example 2.

[0066] Table 3 shows the mask characteristics and resist pattern dimensions on the wafer for a photomask in Example 4, in which the absorbing layer 14 is made of indium oxide and has a thickness of 26 nm, and the outermost layer 15 is made of tantalum oxide and has a thickness of 2 nm. For the reflective photomask 200 of Example 4, no change in film thickness was observed with respect to hydrogen radicals. The OD value was 1.77, and a contrast capable of transferring a pattern was obtained. As a result of patterning using EUV light, the HV bias was 4.6 nm, and compared to Comparative Example 2, the shadowing effect was reduced, resulting in a significant improvement in pattern transferability.

[0067] Table 3 shows the mask characteristics and resist pattern dimensions on the wafer for a photomask in Example 5, in which the absorption layer 14 is made of indium oxide and has a thickness of 26 nm, and the outermost layer 15 is made of bismuth (Bi) and has a thickness of 2 nm. For the reflective photomask 200 of Example 5, no change in film thickness was observed with respect to hydrogen radicals. The OD value was 1.77, and a contrast capable of transferring a pattern was obtained. As a result of patterning using EUV light, the HV bias was 4.6 nm, and compared to Comparative Example 2, the shadowing effect was reduced, resulting in a significant improvement in pattern transferability.

[0068] Table 3 shows the mask characteristics and resist pattern dimensions on the wafer in Comparative Example 1, where the absorbing layer 14 is made of indium oxide (O / In=1.5) with a thickness of 26 nm and the outermost layer 15 is not formed. With the reflective photomask 200 of Comparative Example 1, the OD value was 1.77, and sufficient contrast was obtained. As a result of patterning with EUV light, the HV bias was 4.6 nm, and high transferability was obtained. However, as a result of the hydrogen radical resistance evaluation, there was a film loss of 1 nm immediately after the start of the hydrogen radical treatment, and no film loss was observed thereafter.

[0069] Comparing Examples 1 to 5 with the existing film (Comparative Example 2), the hydrogen radical resistance of each of the reflective photomasks 200 of Examples 1 to 5 was equal to or higher than that of the reflective photomask using the existing film, and the pattern transferability was improved. In addition, a comparison with Comparative Example 1 revealed that the low-reflection portion 18 in which the outermost layer 15 is formed using a material resistant to hydrogen radicals as the main material has higher hydrogen radical resistance than the low-reflection portion 18 formed only from the absorption layer 14. Furthermore, in all of the reflective photomasks 200 of Examples 1 to 5 and Comparative Examples 1 and 2 shown in Table 3, there was no change in film thickness before and after the cleaning treatment, which resulted in the masks having resistance to cleaning.

[0070] As a result, the reflective photomask 200 in which the outermost layer 15 made of a hydrogen radical resistant material is formed on the absorbing layer 14 made of a material having a high k value has excellent transferability and radiation resistance, reduces the projection effect, and has a long life and high transfer performance. In other words, the reflective photomask 200 having the outermost layer 15 made of a hydrogen radical resistant material on the absorbing layer 14 made of a material having a high k value suppresses or reduces the projection effect and has resistance to hydrogen radicals. [Industrial Applicability]

[0071] The reflective photomask blank and reflective photomask according to the present invention can be suitably used for forming fine patterns by EUV exposure in the manufacturing process of semiconductor integrated circuits and the like. [Explanation of symbols]

[0072] 1. Circuit board 2...Reflection layer 3. Capping layer 4. Absorption layer 5...Top layer 6...Reflector 7...Low reflective area 7a Low reflection pattern (absorption pattern) 10. Reflective photomask blank 20. Reflective photomask 11... Circuit board 12...Multilayer reflective film 13. Capping layer 14. Absorption layer 15...Top layer 16 Back conductive film 17...Reflector 18...Low reflective area 18a Low reflection pattern 19. Resist film 19a Resist pattern 100···Reflective Photomask Blank 200···Reflective photomask

Claims

1. A reflective photomask blank for producing a reflective photomask for pattern transfer using extreme ultraviolet light as a light source, comprising: A substrate; A reflecting portion formed on the substrate for reflecting incident light; a low-reflection portion formed on the reflection portion and absorbing incident light, the low-reflection portion is a laminated structure of at least two layers including an absorbing layer and an outermost layer, At least one of the absorption layers of the low reflectance portion contains indium oxide, a reflective photomask blank characterized in that an outermost layer of the low-reflection portion contains one or more of aluminum (Al), silicon (Si), palladium (Pd), zirconium (Zr), hafnium (Hf), niobium (Nb), platinum (Pt), yttrium (Y), nickel (Ni), lead (Pb), titanium (Ti), and gallium (Ga), and their oxides, nitrides, fluorides, borides, oxynitrides, oxyborides, and boron oxynitrides, or contains one or more of fluorides and borides of tantalum (Ta).

2. the absorption layer is formed of a material containing indium (In) and oxygen (O) in a total amount of 50 atomic % or more, 2. The reflective photomask blank according to claim 1, wherein an atomic ratio (O / In) of oxygen (O) to indium (In) is 1 or more and 1.5 or less.

3. The layer containing indium oxide in the absorption layer may be selected from the group consisting of beryllium (Be), calcium (Ca), scandium (Sc), vanadium (V), manganese (Mn), iron (Fe), cobalt (Co), copper (Cu), ruthenium (Ru), silver (Ag), barium (Ba), iridium (Ir), gold (Au), silicon (Si), germanium (Ge), hafnium (Hf), tantalum (Ta), aluminum (Al), palladium (Pd), zirconium (Zr), and tantalum (Ta).

3. The reflective photomask blank according to claim 1, further comprising at least one of zinc (Zr), niobium (Nb), chromium (Cr), platinum (Pt), yttrium (Y), nickel (Ni), lead (Pb), titanium (Ti), gallium (Ga), tellurium (Te), tungsten (W), molybdenum (Mo), and tin (Sn), as well as oxides, nitrides, fluorides, borides, oxynitrides, oxyborides, and boron oxynitrides thereof.

4. 3. The reflective photomask blank according to claim 1, wherein the layer containing indium oxide in the absorption layer further contains at least one of beryllium (Be), calcium (Ca), scandium (Sc), vanadium (V), manganese (Mn), iron (Fe), cobalt (Co), copper (Cu), silver (Ag), barium (Ba), iridium (Ir), gold (Au), silicon (Si), germanium (Ge), hafnium (Hf), aluminum (Al), palladium (Pd), zirconium (Zr), niobium (Nb), yttrium (Y), nickel (Ni), lead (Pb), titanium (Ti), gallium (Ga), tungsten (W), and molybdenum (Mo), and oxides, nitrides, fluorides, borides, oxynitrides, oxyborides, and boron oxynitrides thereof.

5. The low reflection portion has a film thickness of 60 nm or less, Even when the absorbing layer is divided into a plurality of layers, the total thickness of the layers is 17 nm or more and 45 nm or less, 5. The reflective photomask blank according to claim 1, wherein the outermost layer has a film thickness of 1 nm or more.

6. 6. The reflective photomask blank according to claim 1, wherein the outermost layer contains one or more of palladium (Pd), zirconium (Zr), hafnium (Hf), niobium (Nb), platinum (Pt), yttrium (Y), nickel (Ni), and titanium (Ti), and oxides, nitrides, fluorides, borides, oxynitrides, oxyborides, and boron oxynitrides thereof, or one or more of fluorides and borides of tantalum (Ta).

7. A reflective photomask blank described in any one of claims 1 to 6, characterized in that the thickness of the outermost layer is in the range of 1 nm or more and 10 nm or less.

8. A reflective photomask for pattern transfer using extreme ultraviolet light as a light source, A substrate; A reflecting portion formed on the substrate for reflecting incident light; a low-reflection portion formed on the reflection portion and absorbing incident light, the low-reflection portion is a laminated structure of at least two layers including an absorbing layer and an outermost layer, At least one of the absorption layers of the low reflectance portion contains indium oxide, A reflective photomask, characterized in that an outermost layer of the low-reflection portion contains one or more of aluminum (Al), silicon (Si), palladium (Pd), zirconium (Zr), hafnium (Hf), niobium (Nb), platinum (Pt), yttrium (Y), nickel (Ni), lead (Pb), titanium (Ti), and gallium (Ga), and their oxides, nitrides, fluorides, borides, oxynitrides, oxyborides, and boron oxynitrides, or contains one or more of fluorides and borides of tantalum (Ta).

9. the absorption layer is formed of a material containing indium (In) and oxygen (O) in a total amount of 50 atomic % or more, 9. The reflective photomask according to claim 8, wherein an atomic ratio (O / In) of oxygen (O) to indium (In) is 1 or more and 1.5 or less.

10. The layer containing indium oxide in the absorption layer may be selected from the group consisting of beryllium (Be), calcium (Ca), scandium (Sc), vanadium (V), manganese (Mn), iron (Fe), cobalt (Co), copper (Cu), ruthenium (Ru), silver (Ag), barium (Ba), iridium (Ir), gold (Au), silicon (Si), germanium (Ge), hafnium (Hf), tantalum (Ta), aluminum (Al), palladium (Pd), zirconium (Zn), and tantalum (Ta).

10. The reflective photomask of claim 8, further comprising at least one of zirconium (Zr), niobium (Nb), chromium (Cr), platinum (Pt), yttrium (Y), nickel (Ni), lead (Pb), titanium (Ti), gallium (Ga), tellurium (Te), tungsten (W), molybdenum (Mo), and tin (Sn), as well as oxides, nitrides, fluorides, borides, oxynitrides, oxyborides, and boron oxynitrides thereof.

11. 10. The reflective photomask according to claim 8, wherein the layer containing indium oxide in the absorption layer further contains at least one of beryllium (Be), calcium (Ca), scandium (Sc), vanadium (V), manganese (Mn), iron (Fe), cobalt (Co), copper (Cu), silver (Ag), barium (Ba), iridium (Ir), gold (Au), silicon (Si), germanium (Ge), hafnium (Hf), aluminum (Al), palladium (Pd), zirconium (Zr), niobium (Nb), yttrium (Y), nickel (Ni), lead (Pb), titanium (Ti), gallium (Ga), tungsten (W), and molybdenum (Mo), and oxides, nitrides, fluorides, borides, oxynitrides, oxyborides, and boron oxynitrides thereof.

12. The low reflection portion has a film thickness of 60 nm or less, Even when the absorbing layer is divided into a plurality of layers, the total thickness of the layers is 17 nm or more and 45 nm or less, 12. The reflective photomask according to claim 8, wherein the outermost layer has a thickness of 1 nm or more.

13. 13. The reflective photomask according to claim 8, wherein the outermost layer contains one or more of palladium (Pd), zirconium (Zr), hafnium (Hf), niobium (Nb), platinum (Pt), yttrium (Y), nickel (Ni), and titanium (Ti), and oxides, nitrides, fluorides, borides, oxynitrides, oxyborides, and boron oxynitrides thereof, or one or more of fluorides and borides of tantalum (Ta).

14. A reflective photomask described in any one of claims 8 to 13, characterized in that the thickness of the outermost layer is in the range of 1 nm or more and 10 nm or less.

Citation Information

Patent Citations

  • Reflective photo mask, blank thereof, and method of manufacturing semiconductor device using the same

    JP2006190900A

  • Reflective mask blanks, reflective mask, and manufacturing method of semiconductor device

    JP2007273678A

  • Reflection type photomask, reflection type photomask blank, and method of manufacturing the same

    JP2011176162A

  • Radiation source, lithography apparatus, and device manufacturing method

    JP2011530823A

  • Reflective photomask blank and reflective photomask

    JP2019139085A